Typology of rivers and lakes within the Ukrainian part of the Vistula basin (Bug and San) and its compatibility with investigations in Poland - Khilchevskyi, Valentyn K.; Grebin, Vasyl V.; Zabokrytska, Myroslava R.; Solovey, Tatiana V. (Stowarzyszenie Hydrogeologow Polskich, 2020)
This article describes an investigation of the hydrographical network in the Ukrainian part of the transboundary basins of the Bug and San rivers entering the Vistula basin, carried out by the authors using the typology of rivers and lakes in line with the European Union Water Framework Directive (WFD) 2000/60/EC requirements. The typology of the rivers is based on the typology system adopted in Poland. There are 5 abiotic types in the Bug river basin specified within the Ukraine. The small and medium upland rivers on carbonate or loess rocks dominate. Among the large rivers are the Poltva, Rata, Luga and Ryta. Four abiotic types of rivers are distinguished in the Ukrainian part of the San basin. The most numerous group consists of the small upland rivers on flysch rocks of the Carpathians. The analysis of the structure of the river basin networks showed that the small rivers form 98.5% of the total number (3115 rivers) in the Vistula basin within the Ukraine. Only 1.25% of the basin’s rivers form medium rivers. The percentages of large and very large rivers in the total basin streams are, respectively, 0.2 and 0.05%. There are 68 lakes within the Ukrainian part of the Bug basin, the majority of them (48 lakes, or nearly 71%) are in the category of very small lakes. As for the categories of medium and small lakes, each of them has 9 lakes (13%). There are only two large lakes, the Switiaz and Pulemetske (3%).
Keywords: abiotic typology; Bug; San; WFD 2000/60/EC